The Behavior, interspecific and intraspecific relationships in a group of monkeys in captivity: Ateles fusciceps, Cebus capucinus and Cebus albifrons, in an exhibitor of the Parque Histórico Guayaquil, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2014)
The confinement is an extreme situation to monkeys who usually inhabit wide open spaces. In order to assess the confinement effect on the behavior, six monkeys of the following species have been observed in an exhibitor of Parque Histórico Guayaquil: Cebus capucinus (1), C. albifrons (2), and Ateles fusciceps (3); whose conduct on confinement had not been previously documented. Behavior catalogue has been determined and distinguished between states (activities of longer duration, that means of more than two minutes) and events (activities of shorter duration, of some seconds), as well as the frequency and percentage of time spent in events. Focal sampling, onezero, scan and ad libitum were performed. The repertory of social behaviors was similar among individuals but not exactly the same for each one. Agonic states were observed, but in some cases were not such significant and sometimes invalid, however as agonizing events some appealing behaviors have been observed. The group presents a hierarchical order and has a dominant alpha male established (Cebus capucinus). Globally the individuals tolerate the captivity because they present a repertoire of behaviors similar to that shown in wild and have a very low number of agonistic behaviors; however, in long term their social development will be limited and affected.
Keywords: Ateles fusciceps; behavior; captivity; Cebus albifrons; C. capucinus; ethology; monkeys